Alfalfa (Medicago Sativa L) As A Promising Forage In Indonesia - . sajimin (Indonesian Center for Animal Research and Development, 2011)
Alfalfa (Medicago sativa L) or Lucerne is a perennial herbaceous legume with superior forage quality. It is the most important forage crop in the world and it was the first domesticated forage crop. Alfalfa is able to fix nitrogen from the air through a symbiotic relationship with Rhizobium bacteria with N production 7.85 – 10.37 g/m2. Its rooting system can reach 4.5 m that allows it to escape drought. Forage production can reach 15.48 tons of dry matter per ha/year and containing 18.0 – 29.1 % crude protein. Plants can live 3 to 12 years depending on climatic conditions and crop varieties. However, alfalfa is not a tropical plant, thus it has not been widely cultivated in Indonesia. The problem of alfalfa cultivation are high pest attacks and competition with weeds. Therefore, alfalfa cultivation requires attention and good management to obtain optimum yield. Key word: Alfalfa, forage production, nutrition, pest